The Relationship between Political Marriage and the Re-creation of Power and Legitimacy in the Buyid Era - Shakir Dakhel Shibeeb, Researcher; Khadije Alami Corresponding Author, Supervisor Dr.; Nour al-Din Naimati, Consulting Professor Dr. (lark, 2026)
Political developments in Islamic territories in the early fourth century AH were the product of the interaction between individual agency and political structures. As tensions between the institutions of the caliphate and the emirate increased, the influence of individual agency on the balance of power and the maintenance of social stability grew. One of the consequences of this phenomenon was the emergence of political marriage within the institutions of the caliphate and the emirate. The peak of the conflict between the dual institutions of the caliphate and the emirate occurred during the Buyid era. For instance, Mu'izz al-Dawlah conquered Baghdad in 334 AH, thereby allowing the institution of the emirate to dominate the Abbasid caliphate for an extended period. The Buyid emirs employed various methods and strategies to maintain their dominance over the Abbasid caliphs and subordinate emirs. Among these, Buyid statesmen utilized political marriage as an effective tool for managing political affairs. This research raises the question: What was the relationship between political marriage and the reproduction of power and legitimacy during the Buyid era? The argument, based on historical description and analysis, asserts that political marriage during the Buyid era had a direct correlation with conflict management and the consolidation of political power. The study concludes that intermediary institutions, such as judges and scholars, played a significant role in the relationship between political marriage and the enhancement of power and legitimacy during the Buyid era.
Keywords: Political Marriage, Buyid, Legitimacy, Power, Abbasid Caliphate.